Tolerance of Islam, Christianity, and Hinduism in a Plural Society - Subakri, Subakri; Saihan, Saihan (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objective of this study is to ascertain and delineate the manner in which the concept of tolerance is understood and practised by the diverse population of Kedungrejo Village, Rowokangkung District, Lumajang Regency. The village community is a society with a high level of plurality, characterised by the coexistence of diverse religious cultures and sentiments. Nevertheless, there is a clear indication of harmony and mutual respect in everyday life. The village community does not view differences as a cause for conflict; rather, they are regarded as a source of diversity and richness. Consequently, the village community engages in activities and pursuits collectively, irrespective of the discrepancies that exist. This study employs a qualitative approach. The research paradigm is phenomenological or interpretive. A qualitative approach is a paradigm of natural research, which entails developing a theory by drawing upon data derived from the real world. The research location was Kedungrejo Village, Rowokangkung district, Lumajang Regency. The findings of this study indicate that all religions espouse absolutist claims, whether Islam, Christianity, Hinduism, or Judaism. Particularist-subjective monotheistic claims are likely to exacerbate inter-religious conflict, particularly when multiple strong and particularistic religious organisations coexist.